Development of Government Web System in Optimizing Public Administration Services and Information Transparency in Saka State Village - Lestari, Kanti; Saputra, Alfin Dwi (YHMM PUBLISHING, 2025)
Negara Saka Village in Pesawaran Regency faces challenges in delivering fast, equitable, and accurate public information to the community. The lack of use of digital media leads to a low level of access to information by villagers. This research aims to design and implement a Web Government system as a website-based public information media using the System Development Life Cycle (SDLC) method of the Waterfall model, through the stages of identification of needs, system design, implementation, and testing using the Black Box method. Data were collected through interviews, direct observation, and literature studies. The results of the research produced a village government website that is equipped with main features such as village profiles, organizational structure, population data, and the latest news, and has been tested to work according to its function and is easily accessible through computers and mobile devices. The application of the concept of Web Government in an integrated manner at the village level with a responsive and user-friendly system design, which not only functions as an information medium, but also as a means of community participation in village development. This research proves that the implementation of Web Government is able to significantly improve the quality of public information services and the transparency of village government.